Quasi–min–max dynamic output feedback MPC for LPV systems. (10th March 2014) - Huang, Hua; He, De–Feng; Chen, Qiu–Xia
This paper presents a dynamic output feedback model predictive control (MPC) scheme for linear parameter varying (LPV) systems based on quasi–min–max scheme. At each time instant, an optimal control sequence is computed by minimising the upper bound of an infinite horizon quadratic objective function subject to input constraints using linear matrix inequalities (LMIs). A sufficient condition is derived to guarantee robust stability of the closed–loop system and an iterative algorithm involving convex optimisations is presented to solve the online optimisation problem. Finally, two numerical examples were used to demonstrate the effectiveness of the proposed results.